Advanced REIT Portfolio Optimization Innovative Tools for Risk Management - Lindquist, W. Brent; Rachev, Svetlozar T.; Hu, Yuan; Shirvani, Abootaleb (Dynamic Modeling and Econometrics in Economics and Finance, 2022)
XIV, 258 p. 1 illus.